NNN language and evidence-based practice guidelines for acute cardiac care: retaining the essence of nursing. - Van Horn ER; Kautz DD (Dimensions of Critical Care Nursing)
Multidisciplinary management of the acute cardiac patient, for decades, has been driven by best practices, treatment algorithms, and research-based protocols. As nurses continue to develop and implement evidence-based care, they must ensure that the essence of nursing is not lost in the process. In this article, strategies for the development of evidence-based practice guidelines for acute cardiac patients using standardized nursing language are provided.